Nonrecurrent Laryngeal Nerve : A Rare Entity - P., Shrinath D. Kamath; Rathnakar, Pretty; Shetty, Kishore (Journal of Health and Allied Sciences NU, 2012)
The non recurrent laryngeal nerve (nRLN) is a rare abnormal condition that the head and neck surgeon must aware of in order to avoid postoperative morbidity. High index of suspicion, Preoperative recognition of patients with situs inversus, dysphagia lusoria, identification of medialised vagus nerve and meticulous dissection can minimise the risk of injury to nRLN intraoperatively.We are reporting a case of nRLN observed during hemithyroidectomy for a 53 year old female patient.
Keywords: non recurrent laryngeal nerve; hemithyroidectomy; vagus nerve; situs inversus; dysphagia lusoria